2017
DOI: 10.1089/lap.2016.0337
|View full text |Cite
|
Sign up to set email alerts
|

A Provisional Experience with Robot-Assisted Soave Procedure for Older Children with Hirschsprung Disease: Back to the Future?

Abstract: Hirschsprung disease is a congenital disease characterized by intestinal aganglionosis of various extents. Most patients are younger than 1 year of age. Though, a minority of cases can be older or even adult. Older the patient the more difficult and prolonged is the endorectal dissection required for the pull-through procedure. Longer surgery leads to longer anal dilatation and trauma with subsequent higher likelihood of continence impairment. The article aims at describing the first case series of robot-assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 12 publications
1
21
0
Order By: Relevance
“…To the best of our knowledge, our study is the largest series of robotic-assisted surgery for Hirschsprung's disease in infants. The total operative time was shorter than previous reports, especially in the robotic console component (mean, 93.2 min; range: 80 -180 min; mean console time, 57.7 min) [11,13]. The factor that can explain this difference is that our department has a lot of patients with HD and we are trained and operated to use proficient techniques in open surgery, laparoscopic surgery, so when conducted robot surgery, our operative time was shorter than other authors with the advantages of robot surgery.…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations
“…To the best of our knowledge, our study is the largest series of robotic-assisted surgery for Hirschsprung's disease in infants. The total operative time was shorter than previous reports, especially in the robotic console component (mean, 93.2 min; range: 80 -180 min; mean console time, 57.7 min) [11,13]. The factor that can explain this difference is that our department has a lot of patients with HD and we are trained and operated to use proficient techniques in open surgery, laparoscopic surgery, so when conducted robot surgery, our operative time was shorter than other authors with the advantages of robot surgery.…”
Section: Discussionmentioning
confidence: 61%
“…Reduced sphincters stretching and less endorectal dissection are required in robotic surgery compared to conventional laparoscopic surgery. Moreover, easier seromuscular dissection can be performed down to 2–3 cm above the pectinate line in robotic surgery [ 11 , 13 ]. The disadvantages of robotic surgery are well documented.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 In 2017, Mattioli et al reported three cases of robot-assisted Soave procedures for HSCR in children aged 5 years, 16 years and 20 months. 32 According to the postoperative follow-up data of different centers, the clinical results of RAS are satisfactory, with no postoperative incontinence, good defecation function, and a low incidence of postoperative enterocolitis. [32][33][34][35] Prospective studies of small samples found that Soave surgery performed by RAS could be successfully completed without intraoperative complications, and the incidence of postoperative complications was significantly reduced.…”
Section: General Surgerymentioning
confidence: 96%